2016
DOI: 10.1371/journal.pone.0163637
|View full text |Cite
|
Sign up to set email alerts
|

A Total Pleural Covering for Lymphangioleiomyomatosis Prevents Pneumothorax Recurrence

Abstract: BackgroundSpontaneous pneumothorax is a major and frequently recurrent complication of lymphangioleiomyomatosis (LAM). Despite the customary use of pleurodesis to manage pnenumothorax, the recurrence rate remains high, and accompanying pleural adhesions cause serious bleeding during subsequent lung transplantation. Therefore, we have developed a technique of total pleural covering (TPC) for LAM to wrap the entire visceral pleura with sheets of oxidized regenerated cellulose (ORC) mesh, thereby reinforcing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 18 publications
1
38
3
Order By: Relevance
“…Based on these presentations, the conventional treatment approach in which all subpleural cysts and bullae are resected or subjected to pleuredosis is not feasible for the management of PTX in BHDS. Therefore, it is important for pulmonologists and thoracic surgeons to be aware of this rare cause of PTX and to consider a new therapeutic method such as the total pleural covering technique …”
Section: Discussionmentioning
confidence: 99%
“…Based on these presentations, the conventional treatment approach in which all subpleural cysts and bullae are resected or subjected to pleuredosis is not feasible for the management of PTX in BHDS. Therefore, it is important for pulmonologists and thoracic surgeons to be aware of this rare cause of PTX and to consider a new therapeutic method such as the total pleural covering technique …”
Section: Discussionmentioning
confidence: 99%
“…Total Pleural Covering (TPC), which involves wrapping the visceral pleura in a bioabsorbable mesh, has shown promise in preventing pneumothorax without severe impairment of lung function or formation of severe pleural adhesions (96). In a recent study involving 43 patients with LAM, TPC resulted in a pneumothorax recurrence rate (26%) that was comparable to traditional pleurodesis (15, 96). Successful use of TPC has also been reported in PLCH, BHD, bronchiolitis obliterans, and Ehlers-Danlos Syndrome (97, 98).…”
Section: Introductionmentioning
confidence: 99%
“…Since recurrent pneumothorax is one of the most common complications seen in LAM patients, chemical or mechanical were thickened, and minimal adhesion of the visceral to the parietal pleura was evident. e Elastica-Masson stain showed the thickened visceral pleura above the natural visceral pleura (arrow) pleurodesis has been recommended to prevent recurrence [3,4]. However, after pleurodesis, it was difficult to dissect the pleura and control intraoperative bleeding, because of severe adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Although animal experiments have been performed to check adhesion or visceral pleural thickness after pleurodesis [3], no report on a patient treated via TPC who later underwent lung transplantation has appeared. As shown here, TPC might be one of the good tools for prevention of recurred pneumothorax, making the thickened visceral pleura useful to describe our patient with LAM who underwent TPC followed by lung transplantation; examination of the extracted lung showed that our treatment reinforced the visceral pleura in the absence of dense adhesions.…”
Section: Discussionmentioning
confidence: 99%